Isotopic properties of the well-established resonances for γn→ηn in the presence of a narrow exotic resonance; Modern Physics Letters A; Vol. 31, iss. 28 - Tryasuchev V. A. Vladimir Andreevich (Particles and Fields; Gravitation; Cosmology and Nuclear Physics, 2016)
Title screen